Productivity and profitability of citrus nursery operation in Abia State, Nigeria - Iroabuchi, J.N; Odii, M.A.C.A; Emenyonu, C.A; Gbolagun, A.O; Onyeke, A.C; Esogwa, I.E; Akanni, B.A (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The aim of this study was to provide insight on productivity and profitability of citrus nursery operation in Abia State, Nigeria. Data such as socio-economic features of the nursery operators, quantities and prices of inputs and outputs of their operation were obtained through multi-stage sampling techniques from 54 citrus nursery operators. Costs and returns analysis, productivity models and multiple regression analysis were used to analyze the data from the survey. It was shown that majority of the operators were male with average age of 47.98years, year of education of 11.35years and household size of 5 persons. The variable cost of nursery operation was 92.84% of the total cost (N637,117.56) while the fixed cost was 7.16% of the total cost. The revenue from the sales of citrus seedlings was N1,140,856.69 therefore the gross and net margin of the ventures wereN503,739.13 and N454,580.08 respectively. In addition, rate of return on investment was 66.24%. The total factor cost and value of citrus output was N686,276.63 and N1,140,856.69 respectively hence the productivity index of citrus nursery production was 1.66. Results of the regression indicated that costs of labor and planting materials had negative significant while household size, years of experience and access to credit had positive significant effects on the profitability. In conclusion, Citrus nursery operation is dominated by middle - aged, educated, experience with moderate household size. It has good return on investment (ROI) with productivity above unity but high costs of labor and planting materials reduces profitability while household size, years of experience and access to credit enhanced profitability. It was recommended that youth education about gains of citrus nursery production business should be advocated considering its viability and profitability to reduce unemployment and government should prioritized extension of necessary assistance such as inputs subsidy and access to credit to the nursery operators.